E-KTP Service Policy Influences at the Salamrejo Village Office on Public Satisfaction - Sutowo, Sutowo; Nasyirudin, Muhammad; Hermawan, Yusada Andri (Innovative: Journal Of Social Science Research, 2024)
This study aims to determine the effect of the E-KTP public service policy at the Salamrejo Village Office on public satisfaction. The method used is a quantitative research method. This study was conducted in Salamrejo Village, with the sample being the community of Salamrejo Village. To measure the results of the validity of the instrument using validity and reliability tests. Then, the classical assumption test is performed by testing normality and heteroscedasticity—hypothesis testing using the T-test (partial test). From the results of the data analysis, it was found that the E-KTP service policy at the Salamrejo village office significantly influenced public satisfaction by 0.002.